Solving a radical system of equations

preview_player
Показать описание

Рекомендации по теме
Комментарии
Автор

Nice.

To simplify let u = cbrt(x), v = cbrt(y)
Therefore x = u^3, y = v^3

Thus the original equations become
u^3 - v^3 = 7 #1
u^2 + uv + v^2 = 7 #2


Dividing #1 by #2 gives u - v = 1 #3
cubing both sides gives
u^3 - v^3 - 3uv(u-v) = 1
substituting #1 and #3
7 - 3uv(1) = 1
3uv = 6
uv = 2
and the rest follows as before.

echandler
Автор

The problem is interesting, solution as well. Thanks.

prabhudasmandal
Автор

Вот, чтобы не надо было тягать эти кубические радикалы, сделал бы лучше замену

Halleluyah